Student Use of the Information Commons: An Exploration through Mixed Methods - Archambault, Susan Gardner; Justice, Alexander (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – In this case study, librarians at the William H. Hannon Library at Loyola Marymount University explored user behaviour in the Information Commons, user preferences for furniture style and configuration, and how users engaged with a mix of technology, resources, and activities inside the space.Methods – The researchers used a mixed-methods case study consisting of 2,443 “direct observations,” 646 environmental scans, 248 patron surveys, and 46 whiteboard poll questions. They created visualizations of results in Tableau, with filters for zone and variable. They then carried out a follow-up furniture preferences survey with 190 respondents.Results – Independent study dominated the space usage. Users valued spaciousness, quiet, privacy, and a clean environment. Users frequently multi-tasked with additional devices as they simultaneously used the library computers, including cell phones, headphones, and laptops. The majority of students self-reported using a library computer for email and to access the campus online learning platform. They also reported reading/studying and printing as frequent activities, although these were less frequently observed. Unattended belongings were observed along with broken electrical outlets. Temperature and noise levels were highly variable.Conclusions – This methodology allowed for the exploration of space use and satisfaction and uncovered implications for the redesign of the library space. The library has already taken steps toward making improvements based on this assessment project including: removing some reference stacks in favor of additional seating space, an inventory of all electrical outlets, and the exploration of new furniture and noise control strategies.